Navigating Sacred Languages: Paraphrasing the Psalms in Renaissance Scotland - Porter, D. A. (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2022)
Translations and paraphrases of the Biblical psalms were popular throughout early modern Europe. The Latin poetic paraphrase of Psalm 51 by George Buchanan is examined alongside the Scots-language translation of Psalm 2 by Alexander Montgomerie to illustrate some of the complexities of the Renaissance interplay between Latin and vernacular translation, poetics, confession, and politics. Both poets engage with contemporary debates over the meaning of the Biblical texts, and both display a high degree of poetic and rhetorical sophistication in transforming the psalms according to their own interpretative commitments. Each demonstrates close attention towards and care for correct interpretation, and each shows a high degree of freedom in adapting and recreating the polysemous meanings of the original while also applying new meanings to serve their own liturgical, spiritual, and poetic purposes.